Pengaruh Mutu Pelayanan dan Mutu Pemasaran Di Kantor Cabang Pembantu Bank Muamalat Tulungagung Terhadap Kepuasan Nasabah - Moch. Uzeir Mustaqfirin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The Influence of Service Quality and Marketing Quality in The Auxiliary Branch Office of Bank Muamalat Tulungagung on Customer Satisfaction", written by Moch. Uzeir Mustaqfirin. This research was motivated by the desire of researchers to know about Bank Muamalat Auxiliary Branch Office in Tulungagung, especially about the performance of the First Bank Murni Syariah. Researchers want to know about the quality of performance (in terms of service and marketing) owned, whether it affects the satisfaction of customers who use their services. The formulation of the problems in this study there are three, namely: (1) Is there an influence of service quality factors on KCP Bank Muamalat Tulungagung on customer satisfaction? (2) Is there an influence of marketing quality factors on KCP Bank Muamalat Tulungagung on customer satisfaction? (3) Which factor is most dominant in the customer satisfaction at KCP Bank Muamalat Tulungagung? Which factors are most dominant in customer satisfaction at KCP Bank Muamalat Tulungagung? This type of research is field research with a quantitative approach whose problems are descriptive. The sample was taken purposive sample (sample aimed) which is a special customer domiciled in the Tulungagung region and educated at least Diploma amounted to 151 customers. The method of data collection used is the questionnaire method, interview and documentation. While the data analysis technique using SPSS 16.0 with its stages is (1) the validity and reliability test (2) the data normality test (3) the multiple regression analysis test (4) the hypothesis test and (5) the determination coefficient test. Research results: there is a significant influence between the quality of service and the quality of marketing carried out by KCP Bank Muamalat Tulungagung on customer satisfaction. Evident in the coefficients table in each variable X (service quality and marketing quality) obtained sig value. 0.000 compared to sig level. < α = 0.000 < 0.05 and the research hypothesis is tested. Among the quality of service and marketing quality factors carried out by KCP Bank Muamalat Tulungagung, the most dominant factor affecting customer satisfaction of KCP Bank Muamalat Tulungagung is the quality factor of service. Because the quality factor of service has a Fhitung value greater than the marketing quality factor, amounting to 103,007 while the marketing quality factor has a Fhi calculate of 89,840.